2020
DOI: 10.7150/jca.49175
|View full text |Cite
|
Sign up to set email alerts
|

Biological functions and prognostic value of RNA Binding Proteins in clear cell Renal Cell Carcinoma

Abstract: Early detection and accurate evaluation were both critical to improving the prognosis of clear cell Renal Cell Carcinoma (ccRCC) patients. More importantly, RNA Binding Proteins (RBPs) play a vital role in the tumorigenesis and progression of numerous cancers. However, the relationship between RBPs and ccRCC is still unclear. Exploring the potential biological functions of RBPs in ccRCC and establishing a prognostic signature to predict the survival probability remains meaningful. In this study, transcriptome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Renal clear cell carcinoma (ccRCC), specifically its metastatic form, cause high morbidity and mortality among renal cell carcinoma patients 1 . Tumor stemness-associated genes, small copies of tumor genes, promote tumor initiation, invasion, metastasis, and chemical resistance 14 . Several studies indicate that tumor stemness-associated cells are characterized by unlimited proliferation tendency and multiple differentiation potential, playing an essential vital role in developing multi-drug resistance and tumor recurrence 15 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Renal clear cell carcinoma (ccRCC), specifically its metastatic form, cause high morbidity and mortality among renal cell carcinoma patients 1 . Tumor stemness-associated genes, small copies of tumor genes, promote tumor initiation, invasion, metastasis, and chemical resistance 14 . Several studies indicate that tumor stemness-associated cells are characterized by unlimited proliferation tendency and multiple differentiation potential, playing an essential vital role in developing multi-drug resistance and tumor recurrence 15 , 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these results indicated that AC010973.2 might promote tumor growth and survival through negatively regulating apoptosis in ccRCC. Discussion ccRCC, especially metastatic ccRCC, demonstrated high morbidity and mortality in renal cell carcinoma patients 13 . Tumor stemness-associated genes, a small copies of tumor genes, were contributed to tumor initiation, invasion, metastasis and chemical resistance 14 .…”
Section: Ac0109732 Promoted Tumor Proliferation Through Apoptosis Signaling Pathway In Ccrccmentioning
confidence: 99%
“…Recent studies have also indicated that the abnormal expression of some RBPs is involved in the occurrence, proliferation, metastasis, and progression of ccRCC (10-13). Furthermore, prognostic models related to RBPs have also been investigated with database data, which may provide a way to predict the prognosis of ccRCC (14)(15)(16)(17)(18). However, the precise roles of RBPs in ccRCC tumorigenesis and development remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The RBP Musashi-2, a member of the Musashi gene family, has been characterized as an oncoprotein in a variety of tumors, and its aberrant expression is closely associated with tumor occurrence and progression (including in breast, lung, pancreatic, liver, prostate and colorectal cancers) (19)(20)(21)(22)(23)(24) mediated by its participation in the regulation of various molecules and signaling pathways (25). Although some studies that comprehensively analyzed RBPs have shown that multiple prediction models based on RBPs have important guiding significance for the outcome of ccRCC, it is worth noting that these studies were based on increased expression levels of RBPs (15)(16)(17)(18). However, the role and function of Musashi-2 in RCC, particularly in ccRCC, are still not clear, and there are currently no studies on the effects of the RBP Musashi-2 on ccRCC patients.…”
Section: Introductionmentioning
confidence: 99%